1990
DOI: 10.1246/bcsj.63.3467
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of a Heterodetic Cyclic Peptide: Gramicidin S Analog Containing Disulfide Bond

Abstract: In order to investigate the relationship between the structure of a peptide backbone and the formation of an intramolecular disulfide bond (S–S) in the peptide, a linear analog (1) of gramicidin S and a heterodetic cyclic peptide containing an S–S bond (2) were synthesized by the conventional solution method. Since a disulfide bonded compound (2) was easily formed by a treatment of the acetamidomethyl(Acm)-protected linear peptide (1) with iodine in good yield (70%), it is suggested that the mutual position be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Although these peptides commonly have antimicrobial activity against pathogens, there are many variations in their primary structures. For relationship between structure and activity, linearization of cyclic antimicrobial peptides generally alters their activities as well as their ability to interact with cell membranes28–33. Furthermore, Peng et al reported that the positive patch and the hydrophobic surface were both important for the antifungal function of Pa ‐AMP from poke weed ( P. americana ) seeds34.…”
Section: Discussionmentioning
confidence: 99%
“…Although these peptides commonly have antimicrobial activity against pathogens, there are many variations in their primary structures. For relationship between structure and activity, linearization of cyclic antimicrobial peptides generally alters their activities as well as their ability to interact with cell membranes28–33. Furthermore, Peng et al reported that the positive patch and the hydrophobic surface were both important for the antifungal function of Pa ‐AMP from poke weed ( P. americana ) seeds34.…”
Section: Discussionmentioning
confidence: 99%
“…Linearization of cyclic antimicrobial peptides generally alters their activities as well as their ability to interact with membranes (9)(10)(11)(12)(13)31,38,39). Matsuzaki et al have shown that a linear analog of tachyplesin I, where all four SH groups of Cys residues are protected with acetamidomethy groups, exhibited more membrane disruption but much weaker membrane permeabilization activity than the parent peptide (11,13).…”
Section: Discussionmentioning
confidence: 99%
“…Acyclization of membrane-acting cyclic peptides generally reduces their potencies (Erlanger & Goode, 1954, 1959Makisumi et al, 1971a,b;Satoh et al, 1990;Tamamura et al, 1993a). However, the detailed mechanisms are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Acyclization of gramicidin S •Abstract published in Advance ACS Abstracts, October 1, 1993. 1 Abbreviations: T-SS, tachyplesin I; T-Acm, an acyclic tachyplesin I analog with the four SH groups of tachyplesin I protected by acetamidomethyl groups; NMR, nuclear magnetic resonance; FTIR-PATR, Fourier transform infrared polarized attenuated total reflection; RP-HPLC, reversed-phase high-performance liquid chromatography; CD, circular dichroism; PC, egg yolk L-a-phosphatidylcholine; PG, L-aphosphatidylglycerol enzymatically converted from PC; LUVs, large unilamellar vesicles. ( Erlanger & Goode, 1954, 1959 and related peptides (Makisumi et al, 1971a,b;Satoh et al, 1990) significantly reduces their potencies. Thus, we synthesized a linear tachyplesin I derivative (T-Acm) in which the four SH groups of tachyplesin I were protected with Acm (acetamidomethyl) groups (Figure 1).…”
mentioning
confidence: 99%